Intelligence theory key questions and debates - Gill, Peter, 1947-; Marrin, Stephen; Phythian, Mark (Studies in intelligence series, 2009)
Containing essays by some of the key theorists in the field from the US, UK and Canada, this volume assesses the role and utility of theory in intelligence studies.